The effect of profitability, carbon emissions disclosure, sustainability reporting, and green accounting on the firm value of Indonesia energy companies: Pengaruh profitabilitas, pengungkapan emisi karbon, laporan keberlanjutan, dan akuntansi hijau terhadap nilai perusahaan sektor energi Indonesia - Al Gamar, Moh. Frisal; Widoretno, Astrini Aning (Universitas Pamulang, 2024)
This study examines the effects of profitability, carbon emissions disclosure, sustainability reporting, and green accounting on the firm value of energy sector businesses listed on the Indonesian Stock Exchange (IDX). We employed linear regression analysis with panel data from 16 different companies. These samples were selected using a purposive sampling approach, and 80 were evaluated. The findings indicate that the disclosure of sustainability reports and green accounting notably impact firm value. However, disclosure of carbon emissions does not affect firm value. Firm value is significantly determined by profitability. The study's findings emphasize the importance of openness and social accountability through sustainability reports and green accounting, offering valuable stakeholder insights.